Strategie d'impresa e processi di etnicizzazione in alcuni percorsi lavorativi di migranti - Gianfranca Ranisio (EtnoAntropologia)
In this article I focus on a specific strategy adopted by some entrepreneurs, who have made ethnic business in the fields of fast-food and trade in Naples and surroundings. Some authors have pointed out that globalization has produced the “business of ethnicity” and that often the “ethnicizated” appear on the global market as sellers of their own culture. I will consider, on the one hand, the fact that they belong to transnational communities, and on the other hand, the effects of their activities in the urban context by adapting the supply to a demand for products that can be connoted as exotic or “ethnic”. The working paths of some migrants presented in this paper lead us to reflect on the ethnicization process and how that process can become a way through which people stand on the global market.